2022
DOI: 10.1101/2022.08.17.504347
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The centromere/kinetochore is assembled through CENP-C oligomerization

Abstract: The kinetochore is an essential protein complex for accurate chromosome segregation. The constitutive centromere-associated network (CCAN), a subcomplex of the kinetochore, associates with centromeric chromatin providing a platform for the kinetochore assembly. A CCAN protein, CENP-C, is thought to be a central hub for the centromere/kinetochore organization. However, the crucial role of CENP-C in centromeres remains to be elucidated. Here, we demonstrated that both the CCAN-binding domain and C-terminal Cupin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…Second, alignment efficiency depends on microbead size, implying that the NDC80-NUF2-mediated biorientation benefits from an expanded platform for outer kinetochore assembly. Such platform expansion may be attributed to the evolution of the inner kinetochore, which possesses self-oligomerization activity 41,42 , and the centromere, which contains active DNA arrays that extend ∼0.3–4.8 Mbps in humans 43 . The platform of microbeads that we used in this study is an order of magnitude larger than the native kinetochore, which we suggest helps the establishment of a biorientation-like state by the NDC80-NUF2 branch alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, alignment efficiency depends on microbead size, implying that the NDC80-NUF2-mediated biorientation benefits from an expanded platform for outer kinetochore assembly. Such platform expansion may be attributed to the evolution of the inner kinetochore, which possesses self-oligomerization activity 41,42 , and the centromere, which contains active DNA arrays that extend ∼0.3–4.8 Mbps in humans 43 . The platform of microbeads that we used in this study is an order of magnitude larger than the native kinetochore, which we suggest helps the establishment of a biorientation-like state by the NDC80-NUF2 branch alone.…”
Section: Discussionmentioning
confidence: 99%
“…Second, alignment efficiency depends on microbead size, implying that the NDC80-NUF2-mediated biorientation benefits from an expanded platform for outer kinetochore assembly. Such platform expansion may be attributed to the evolution of the inner kinetochore, which possesses self-oligomerization activity 41,42 , and the centromere, which contains active DNA arrays that extend ~0. 3-4.8 Mbps in humans 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CENH3-tailswap-GFP fusion proteins with intact Cterminal domains show loading onto chromosomes during mitosis but not meiosis, which implies differential control between these cell types mediated via N-terminal tail interactions (Ingouff et al 2007;Ravi et al 2011). Recent work has shown that oligomerization of mammalian inner kinetochore proteins, such as CENP-C (Hara et al 2023) and CENPT (also known as CENP-T) (Sissoko et al 2024), can stabilize and protect CENP-A loading and promote kinetochore assembly. As CENP-C is conserved in plants (Ogura et al 2004;Du and Dawe 2007), similar oligomerization mechanisms may operate during plant kinetochore formation (Fig.…”
Section: Cenh3 Homeostasis Within Plant Centromeresmentioning
confidence: 99%
“…Interactions between the CENH3 loader complex and kinetochore factors may create feed-forward recruitment of CENH3. (C) As the density of CENH3containing nucleosomes increases, the region undergoes stabilization and compaction of the centromeric chromatin, potentially facilitated by oligomerization of inner kinetochore proteins, for example, CENP-C or KNL2 (Hara et al 2023;Sissoko et al 2024). VIM1 (orange) is known to bind and maintain methylation at CG sites and contributes to centromere "strength," potentially via promotion of kinetochore multimerization.…”
Section: Cenh3 Homeostasis Within Plant Centromeresmentioning
confidence: 99%
“…The cells images were acquired by the confocal microscopy with spinning-disc. The chromosome alignment was analyzed according to a previous report 39 . Briefly, The XY positions of CENP-A signals in mitotic cells were acquired using Imaris software and plotted on a two-dimensional plane.…”
Section: Chromosome Alignment Assaymentioning
confidence: 99%